Settlement of State Administration Disputes in the Election of Governors, Regents and Mayors To Create Fair Elections - Rahim, Erman I; Rahmi, I.G. Ayu Ketut; Riewanto, Agus (Law Research Review Quarterly, 2018)
The purpose of writing this is described and analyze dispute resolution administrative in the election of the governor, regents and mayors for realize fair elections .A method of approach that is used is doctrinal and confirming empirical based on data and information related to the holding of an election common, then analyzed a sort of descriptive set qualitative .The results showed that writing candidate couple who were cheated and objections on the decision general election commission provincial or districts and city on the provision of candidate couple participants election given the opportunity suing the determination of the decision . The fact that there are under the authority of the with the resolution of disputes state administrative that have been undertaken by by a proctor the selection of the north west frontier province on the great commission nor of the approximately districts and cities in the country with of the judiciary state administrative give rise to multi the prevailing interpretation of the result in the occurrence inconsistency so as to affect phases of the election of a new , even harmful position with respect to the slate and the committee for .Through legal approach normative the resolutions of disputes the forest law enforcement governance usaha negara in the election of the governor , regents and mayors he or she needs the structuring and completion of ketentuan-ketentuan which regulates regional with the resolution of disputes the forest law enforcement governance usaha negara in the election of the governor, regents and mayors .